Gestão de riscos na administração pública : uma proposta de contribuição para o gerenciamento de riscos na Universidade Federal de Sergipe - Lima, Rivaldo José Rodrigues de (2022)
Over the last few decades, the need to manage uncertain events with the potential to impact the achievement of business strategies and objectives, which is conventionally called organizational risks, has been a constant concern in organizations that seek to put themselves in a position to reasonably understand their causes and, above all, consequences, whether negative or positive, in order to adopt the most appropriate measure in the eagerness to treat them. In this sense, risk management emerges as a control mechanism that can offer a structured set of instruments and procedures aimed at identifying and dealing with risks that affect the organization's activities, strategy and objectives, whether private or public. In Public Administration, much more than recommendable, the implementation of risk management is mandatory, which can be inferred from the various normative instruments issued over the last few years, such as, among others, Complementary Law 101/2000; of the Joint Normative Instruction MP/CGU No. 01/2016; of Law 13,303/2016; and Decree No. 9.203/2017. Thus, this research focuses on risk management, especially in Public Administration, with the main objective of formulating a contribution proposal for risk management at the Federal University of Sergipe - UFS, in a way that is viable and aligned with reality and need of the organization. For this purpose, a qualitative approach was used to the research, framing it as exploratory in terms of its objectives, and outlined as a case study, having as sources of evidence interviews that were carried out with those responsible for risk management both at the UFS and in two other federal educational institutions, as well as similarly collected documentation, from which it was possible to extract that the implementation of risk management at UFS is at an advanced stage in terms of the issue of normative instruments related to the subject and which aim to regulate the implementation and execution of the proposed procedures, but, on the other hand, it is still at an incipient stage with regard to the dissemination of the risk management culture among the servers and units of the institution. Likewise, it was found that the risk monitoring and control actions lack better detailing in the institution's Risk Management and Control Plan for the period 2021/2022. In the end, based on the examination of the collected data, it was concluded that there was an opportunity to formulate a proposal for a risk monitoring and control plan, which is part of the textual body of this study.